A RELIGIÃO COMO PROCESSO PEDAGÓGICO NO PENSAMENTO DE MEISHU-SAMA: UM DIÁLOGO COM PAULO FREIRE - Dinelli, Lilia (2011)
The present research intends to contribute to the relation field between religion and education, specifically the concept of religion as an educational process ac-cording to the thought of Meishu-Sama, founder of the Church of World Mes-sianity. The research is divided into three parts. At first, it presents the life of Meishu-Sama and the history of foundation of the Messianic Church, which oc-curred in the first half of the twentieth century in Japan. In the second part, the concept of Meishu-Sama on the function of religion and its relation with educa-tion is studied, especially in the key challenge for the development of human being. In the third part, a dialogue between the educational thoughts of Paulo Freire and Meishu-Sama is established, especially the challenge of humanizing and notions of banking education and liberating dialogue (Paulo Freire) and dead education and living education (Meishu-Sama). In this dialogue it is given emphasis to the notion spiritual education of Meishu-Sama, who con-siders fundamental to critic the disbelief of the modern world regarding the spiritual world . For this author, deconstructing the materialistic thought and integrating the human nature is the task of religion as much as of education.